Environmental Impact Assessment of Heat Storage System in Rock-Bed Accumulator - Mateusz Malinowski; Stanisław Bodziacki; Stanisław Famielec; Damian Huptyś; Sławomir Kurpaska; Hubert Latała; Zuzanna Basak (Energies)
The use of a rock-bed accumulator for a short-term heat storage and air exchange in a building facility is an economical and energy-efficient technological solution to balance and optimize the energy supplied to the facility. Existing scientific studies have not addressed, as yet, the environmental impacts of using a rock bed for heat storage. The purpose of the research is the environmental life cycle assessment (LCA) of a heat storage system in a rock-bed accumulator supported by a photovoltaic installation. The boundaries of the analyzed system include manufacturing the components of the storage device, land preparation for the construction of the accumulator, the entire construction process, including transportation of materials, and its operation in cooperation with a horticultural facility (foil tunnel) during one growing season, as well as the photovoltaic installation. The functional unit in the analysis is 1 square meter of rock-bed accumulator surface area. SimaPro 8.1 software and Ecoinvent database were used to perform the LCA, applying the ReCiPe model to analyze environmental impact. The analysis showed the largest negative environmental impact occurs during raw materials extraction and component manufacturing (32.38 Pt). The heat stored during one season (April to October) at a greenhouse facility reduces this negative impact by approx. 7%, mainly due to the reduction in the use of fossil fuels to heat the facility. A 3 °C increase in average air temperature results in an average reduction of 0.7% per year in the negative environmental impact of the rock-bed thermal energy storage system.